The effect of using the SWOM strategy on creative thinking in mathematics among fourth-grade female students (Journal of the College of Basic Education, 2022)
The aim of the current research is to find out "the effect of using the SWOM strategy on creative thinking in mathematics among fourth-grade female students."To achieve the aim of the research, the following null hypothesis was formulated:There is no statistically significant difference at the level (0.05) between the mean scores of the students of the experimental group who study mathematics according to the SOM strategy and the average scores of the students of the control group who study mathematics according to the usual method in the creative thinking test.